Role of dyslipidemia in the development of nephropathy in patients with type 2 diabetes mellitus (literature review) - S.I. Ismailov; S.U. Muminova (Mìžnarodnij Endokrinologìčnij Žurnal, 2019)
A literature review describes the role of dyslipidemia in the development of nephropathy in patients with type 2 diabetes mellitus. Chronic hyperlipidemia in diabetes is accompanied by damage and dysfunction of various organs and tissues due to a specific generalized change in the microvasculature or microangiopathy. Micro- and macroangiopathies lead to increased cardiovascular mortality in patients with type 2 diabetes mellitus. In patients with diabetes and chronic kidney disease, dyslipidemia can be exacerbated by hyperglycemia and insulin resistance. Control of dyslipidemia is an important therapeutic target, normalization of lipid metabolism and glycemic status reduces the risk of renal complications in type 2 diabetes mellitus.